FINANCIAL AND BUSINESS CYCLES IN TURKEY (Third Sector Social Economic Review, 2023)
The 2008 Global Financial Crisis has drawn attention to the interaction between the financial sector and the real sector. In this study, the relationship between financial cycles and business cycles in Turkey is analyzed for the period 1987:1-2021:3. Industrial production index is used as a proxy for business cycles; and credit, stock prices, real effective exchange rate (REER) and foreign portfolio investments are used as proxies for financial cycles. Financial and business cycles are measured using turning point analysis, Hodrick-Prescott (HP) filter and Baxter-King (BK) filter, and then the synchronization and causality between the cycles are examined. Finally, the time-variation of the relationship between cycles is estimated with the DCC-GARCH model. According to the findings, while stock prices and foreign portfolio investments exhibit leading behavior, credit exhibits lagging behavior and REER exhibits coincident or lagging behavior. According to the results of Granger Causality Analysis, there is causal flow from all variables used to represent financial cycles to business cycles. However only the one between the credit-to-GDP ratio and business cycles is bidirectional. The results of the DCC-GARCH analysis suggest that the ability of financial cycles and business cycles to comove increases during crisis periods. The variable with the highest co-movement ability with business cycles is foreign portfolio investments. Considering all the results, it is concluded that financial cycles lead business cycles and are the cause of business cycles in Turkey.
Keywords: financial Cycle; business cycle; financial-real transmisson channels; DCC-GARCH; filtering